Simplifying Forehead Reconstruction: A Review of More Than 200 Cases - Quatrano, Nicola A.; Dawli, Tamara B.; Park, Andrew J.; Samie, Faramarz H. (Facial Plastic Surgery, 2016)
The forehead is a unique facial region with distinct boundaries and variability in shape from patient to patient. When reconstructing the forehead, it is critical to take into account the regional boundaries as their distortion may result in noticeable facial asymmetry. We propose subdividing the forehead into newly defined zones and put forth a rational algorithm for forehead repair based on these divisions. We retrospectively reviewed a single surgeon's (F. H. S.) experience with Mohs excision and immediate reconstruction of the forehead over a 3-year period. A total of 227 consecutive post-Mohs forehead reconstructions were identified, and the reconstructive technique for a given defect size and location and postoperative complications were recorded. The average patient age was 69 years and 114 (50%) patients were female. Reconstructive techniques varied based on defect size and location within the five distinct forehead zones. Primary closure was the favored technique when appropriate, with variation in orientation based on forehead zone. Modified Burow's advancement flap was the most commonly utilized reconstruction for defects of midlateral forehead and suprabrow area, accounting for 51.7 and 62.5% of repairs, respectively. Other techniques included A-to-T flaps, rotation flaps, and full-thickness skin grafting. Using our defined zones, most common repair techniques, and final outcomes, a reconstructive algorithm for post-Mohs excisions on the forehead was derived. Consideration of the five distinct forehead zones and application of an algorithm to guide technique selection for post-Mohs forehead defect repair can lead to consistent results.
Keywords: forehead reconstruction; facial subunits; forehead zones; reconstruction algorithm; Mohs surgery